Peran Religiusitas Dan Religiusitas Dalam Mencari Bantuan Psikologis Pada Mahasiswa Di Semarang - Diany Ufieta Syafitri; Laily Rahmah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Mental health problems are increasingly prevalent in Indonesia, but many people are still reluctant to seek professional psychological help. Religiosity is considered as one of the factors that can influence one's preference for seeking psychological help, especially in Indonesian society, specifically in the city of Semarang, Central Java, which the life of society closely related to the value of religiosity. Therefore this study aimed to see the contribution of religiosity and religious coping in influencing the search for psychological help. This research was conducted at two universities, one state university and one Islamic private university which were determined through random sampling. Data collection was carried out online and offline with the Indonesian Islamic Psychological Measure of Islamic Psychology (I-PMIR), Islamic Religious Coping Scale (RCOPE), Attitude Towards Seeking Psychological Help (ATSPH), and Mental Health Seeking Help Intentions Scale (MHSIS) and obtained a total of 731 respondents. Multiple regression analysis showed that attitude was the strongest predictor of intention to seek psychological help (B= 0,556, p<0,01), followed by religious coping (B= 0,08, p<0,01), while religiosity was not a significant predictor. Further analysis showed the unique contribution of religious coping aspects towards the intention of seeking psychological help with F (5, 725) = 8,721, p<0,01, R 0,238. There were also differences in the contribution of religiosity and religious coping to the intention of seeking psychological help based on the background of the respondent (state or private Islamic university) which discussed further in the article.